Implementation of Policy for Establishing License Policy at Department of Investment and One-Door Integrated Licensing Services (DPM & PPTSP) in Binjai - Amru Zuhri Harahap; Isnaini Isnaini; Maksum Syahri Lubis; Rudi Salam Sinaga (Budapest International Research and Critics University, 2021)
The aims of this study is to describe Implementation of Policy for Establishing License Policy at Department of Investment and One-Door Integrated Licensing Services (DPM & PPTSP) in Binjai. This study use qualitative research. Based on the descriptions that the researcher has put forward in the previous chapters, in this chapter the author will draw some conclusions from the results of the field research that the author has done so far and provide suggestions as the last step in this research. In the first year of IMB implementation with OSS there were 732 reports and actions that had been carried out the percentage was 90%. In the second year of IMB implementation with OSS there were 647 reports and actions that had been carried out, the percentage was 89%. In the third year of IMB implementation with OSS, there were 213 reports and actions that had been carried out, the percentage was 81%. So there is a decrease in the issuance of permits in IMB with OSS for actions that have been taken from the first year of implementation to the third year of implementation by 9%.